Interface Shear Behaviour and Modelling of Ultra-High Performance Concrete - Zhou, Mi (University of Waterloo, 2026)
The use of ultra-high-performance concrete (UHPC) in bridge construction has expanded considerably in recent years due to its exceptional mechanical properties, particularly its high compressive strength and superior post-cracking tensile resistance and deformation capacity. One particularly common and critical application of UHPC is its use in the connections of prefabricated structural components. Therefore, understanding UHPC shear resisting performance is essential. To investigate the broadly varying and complex shear stress conditions that can develop in connection regions of modern concrete structures, an experimental program involving UHPC push-off specimens subjected to combined shear and lateral loading was performed. Comparisons of existing shear strength estimation procedures and the applicability of classical concrete failure criteria to unreinforced UHPC interfaces was examined. The findings provide insight into the shear transfer mechanisms of unreinforced UHPC interfaces under varied stress conditions, clarify the influence of external loading on UHPC interface shear strength, and provide a basis for refining design models for UHPC structural connections. Dog-bone direct tension tests were also conducted to investigate the tensile behaviour of UHPC, given the substantial influence of tensile properties on interface shear response. The results demonstrated that UHPC casting volume/size have a significant effect on the measured tensile properties, and therefore would influence the interface shear behaviour. Finite element modelling of UHPC interfaces was performed to validate a proposed smeared-crack modelling approach in which UHPC was incorporated using an adapted tensile behaviour model originally developed for steel fibre-reinforced concrete (SFRC). Comparisons between experimental and numerical results were conducted to validate the accuracy of the proposed modelling approach for UHPC. The findings demonstrate that incorporating a user-defined UHPC, DEM-calibrated, tensile constitutive model calibrated enhanced the predictive capability for UHPC interface behaviour under shear-dominated multiaxial loading.
Keywords: interface shear; UHPC; finite element modelling; push-off testing; concrete crack kinematics